Pioneering Healthcare Law Essays in honour of Margaret Brazier - Farrell, Anne-Maree (Taylor & Francis, 2016)
This book celebrates Professor Margaret Brazier's outstanding contribution to the field of healthcare law and bioethics. It examines key aspects developed in Professor Brazier's agenda-setting body of work, with contributions being provided by leading experts in the field from the UK, Australia, the US and continental Europe. They examine a range of current and future challenges for healthcare law and bioethics, representing state-of-the-art scholarship in the field.